2017
DOI: 10.1111/bjh.14498
|View full text |Cite
|
Sign up to set email alerts
|

Marizomib for central nervous system‐multiple myeloma

Abstract: Marizomib, a natural marine product, is an irreversible proteasome inhibitor currently under investigation in relapsed-refractory multiple myeloma (RRMM) and malignant glioma. Central nervous system-multiple myeloma (CNS-MM) is a rare manifestation of extra-medullary disease with few therapeutic options, highlighting the unmet clinical need in these patients. Marizomib demonstrated encouraging activity in RRMM and has emerging clinical activity in glioma, making it a potential CNS-MM therapeutic intervention. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 9 publications
0
31
0
1
Order By: Relevance
“…Encouraging phase I/II clinical trial results in relapsed/refractory MM patients led to completion of a phase I study evaluating marizomib, pomalidomide and dexamethasone in heavily pre‐treated patients with relapsed/refractory disease (Richardson et al , ; Spencer et al , ). With an ORR of 53% and clinical benefit rate of 64%, this new proteasome inhibitor will probably be examined in more advanced clinical trials in the near future, not only for its ability to re‐sensitise patients to proteasome inhibition but for its activity in MM involving the central nervous system (Badros et al , ). Oprozomib is structurally similar to carfilzomib with the advantage of being orally administered and has demonstrated pre‐clinical efficacy in bortezomib‐resistant MM cells (Chauhan et al , ).…”
Section: Later‐generation Proteasome Inhibitorsmentioning
confidence: 99%
“…Encouraging phase I/II clinical trial results in relapsed/refractory MM patients led to completion of a phase I study evaluating marizomib, pomalidomide and dexamethasone in heavily pre‐treated patients with relapsed/refractory disease (Richardson et al , ; Spencer et al , ). With an ORR of 53% and clinical benefit rate of 64%, this new proteasome inhibitor will probably be examined in more advanced clinical trials in the near future, not only for its ability to re‐sensitise patients to proteasome inhibition but for its activity in MM involving the central nervous system (Badros et al , ). Oprozomib is structurally similar to carfilzomib with the advantage of being orally administered and has demonstrated pre‐clinical efficacy in bortezomib‐resistant MM cells (Chauhan et al , ).…”
Section: Later‐generation Proteasome Inhibitorsmentioning
confidence: 99%
“…Recently, higher doses of MRZ infused for a shorter duration (0·8 mg/m 2 , 10 min IV infusion) have been administered under compassionate use in a limited number of MM patients with CNS relapse (CNS‐MM). This dosing schedule, which is identical to the schedule being evaluated in glioma, appears to be well tolerated in CNS‐MM patients and is showing promising signs of clinical benefit (Badros et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Marizomib irreversibly inhibits the three proteolytic sites of the 20S proteasome and pre-clinical studies have shown efficacy in Bortezomib-resistant MM cells [32]. A phase I study evaluating Marizomib, Pomalidomide and Dexamethasone in heavily pre-treated patients with relapsed/refractory MM demonstrated an impressive ORR of 53% and clinical benefit rate of 64% [33][34][35]. This new proteasome inhibitor will likely be examined in more advanced clinical trials in the near future, not only for its ability to re-sensitise patients to proteasome inhibition but for its activity in MM involving the central nervous system.…”
Section: Later-generation Proteasome Inhibitorsmentioning
confidence: 99%